Enzymatic, morphological, and genotoxic effects of benzo[a]pyrene in rainbow trout (Oncorhynchus mykiss) - Fanali, Lara Zácari [UNESP]; De Oliveira, Classius [UNESP]; Sturve, Joachim (Springer Nature, 2021)
Fish have defense systems that are capable of repairing damages caused by xenobiotics like benzo[a]pyrene (BaP), so the aims of this study were to identify BaP toxicity in melanomacrophages (MMs) cytoskeleton, evaluate the melanin area in MMs, and analyze genotoxicity. Rainbow trout juveniles (n = 24) were split in 48h and 7d treatments that received 2 mg/kg of BaP. After the experiment, blood samples were collected and liver was removed, to proceed with the analysis: EROD activity, MMs melanin area quantification, melanosomes movements, and a genotoxicity test. The results revealed increased in EROD activity after 48-h and 7-day BaP exposure. The group 7d displayed a reduction in MMs pigmented area, melanosomes aggregation, in addition to an increased frequency of micronucleus. By means of the EROD assay, it was possible to confirm the activation of BaP biotransformation system. The impairment of the melanosomes’ movements possibly by an inactivation of the protein responsible for the pigment dispersion consequently affects the melanin area and thus might negatively impact the MMs detoxification capacity. In addition to this cytotoxicity, the increased frequency of micronucleus might also indicate the genotoxicity of BaP in this important fish species.
Keywords: Cytoskeleton; EROD; Erythrocytes abnormalities; Liver; Melanomacrophage; Morphological alteration